2003
DOI: 10.1590/s0102-35862003000500008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre a eficácia da aerostasia pulmonar, em modelo animal, utilizando diferentes tipos de suturas

Abstract: 295Estudo sobre a eficácia da aerostasia pulmonar, em modelo animal, utilizando diferentes tipos de suturas Estudo sobre a eficácia da aerostasia pulmonar, em modelo animal, utilizando diferentes tipos de suturas * Study about the ability of the pulmonary aerostasia, in animal model, using differents parenchymal pulmonary types of the sutures DARCY Resultados: A média de pressão em que se observou perda do hermetismo pulmonar foi de 29cmH 2 O no tipo 1 (n = 10); 38,5cmH 2 O no tipo 2 (n = 10); 44cmH 2 O no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This suture reinforcement in the stapling line is also recommended by other authors and can be performed with additional stapling or with manual suturing over the area of air leakage [5,23,25]. Complementing the staple line with other surgical sutures or devices could guarantee better resistance at supraphysiological levels of ventilatory pressure [26][27][28]. However, this was not evaluated in our study.…”
Section: Discussionmentioning
confidence: 88%
“…This suture reinforcement in the stapling line is also recommended by other authors and can be performed with additional stapling or with manual suturing over the area of air leakage [5,23,25]. Complementing the staple line with other surgical sutures or devices could guarantee better resistance at supraphysiological levels of ventilatory pressure [26][27][28]. However, this was not evaluated in our study.…”
Section: Discussionmentioning
confidence: 88%
“…These results are in accordance with those obtained by various authors. (9)(10)(11)(12)(13)(14) The incidence of fistulas has also been less frequent after mechanical suture, (15,16,26) although some authors have found the frequency of this complication to be higher. (17,27) The rupture pressure values obtained by various authors suggest that the process of cicatrization can have a beneficial effect on the increased resistance to pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing manual and mechanical sutures of the bronchial stump show that the latter is more resistant on post-operative day 14, (9,10) that it is more resistant from post-operative day 1 to post-operative day 14, (11)(12)(13) especially when covered with bovine pericardium and biological glue, (14) and that it presents a lower incidence of BPF. (4,6,14,15) It is accepted that, although mechanical suture is safe, easily performed, and rapid, it is not totally free of complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation